Comparative Analysis of Kalam Interpretations of Bait al-Maqdis Verses in Sunni, Mu'tazilah, and Shi'a Exegeses - Mujadidi, Haidar Ahmad; Ariyadi , Samsul; Huda , Ade Naelul (Suhuf: International Journal of Islamic Studies, 2025)
This study aims to analyze the comparative interpretation of the verses of Bait al-Maqdis by scholars of kalam schools of thought, namely Sunni, represented by Tafsir Mafātīḥ al-Ghaib by Fakhr al-Dīn ar-Rāzī; Mu'tazilah, represented by Tafsir Al-Kasysyāf by Az-Zamakhshari; and Shi’a, represented by Tafsir Al-Qummī by ‘Alī bin Ibrāhīm Al-Qummī. It also seeks to contextualize the comparative analysis of the interpretations of Bait al-Maqdis verses. This research employs a library research method, with data presentation arranged thematically. For data processing, the researcher uses the content analysis method. The findings reveal that the interpretations of the Sunni and Mu'tazilah kalam schools share many similarities, while the interpretations of the Shi’a kalam school tend to differ, often reflecting sectarian ideologies. The conclusion of this article emphasizes that to liberate Bait al-Maqdis from modern-era colonialism, the Muslim community must seriously prioritize the issue of Bait al-Maqdis as a central concern and study it with accurate knowledge, including the interpretation of Bait al-Maqdis verses, to avoid biased interpretations influenced by specific sectarian tendencies.